Perioperative Complications of Esophageal Atresia - Morini, Francesco; Conforti, Andrea; Bagolan, Pietro (European Journal of Pediatric Surgery, 2018)
Current survival rate of infants with esophageal atresia with/without tracheoesophageal fistula (EA/TEF) exceeds 90% and great interest is dedicated to the long-term outcomes and complications. However, perioperative complications represent a significant burden to the EA/TEF infants and a technical challenge for the surgeon. In this review, we will focus on the most frequent perioperative complications specific of EA/TEF to describe their predisposing factors, possible preventive measures, and treatment options.
Keywords: anastomotic leak; chylothorax; recurrent fistula; thoracoscopy; vocal cord dysfunction